ENDOMETRIOSIS IN A POSTMENOPAUSAL WOMAN - IGOR S. Zakharov; LYUBOV N. Petrich; YULIYA V. Vasyutinskaya; TAMARA N. Demyanova; LARISA E. Fetischeva (Фундаментальная и клиническая медицина)
There is a widespread opinion that endometriosis is a disease specific for the childbearing period; however, there is extensive evidence on its occurrence also in postmenopausal women, with a prevalence reaching 5%. Since the malignant transformation of endometriosis is a rare but hazardous event, here we describe a case report of asymptomatic retroperitoneal endometriosis in a postmenopausal woman. Upon the excision of neoplasm, a histological examination confirmed endometriosis.